Microglial Implication in Parkinson’s Disease: Loss of Beneficial Physiological Roles or Gain of Inflammatory Functions? - Lecours, Cynthia; Bordeleau, Maude; Cantin, Léo; Parent, Martin; Paolo, Thérèse Di; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2018)
Microglia, often described as the brain-resident macrophages, play crucial roles in central nervous system development, maintenance, plasticity, and adaptation to the environment. Both aging and chronic stress promote microglial morphological and functional changes, which can lead to the development of brain pathologies including Parkinson’s disease (PD). Indeed, aging, and chronic stress represent main environmental risk factors for PD. In these conditions, microglia are known to undergo different morphological and functional changes. Inflammation is an important component of PD and disequilibrium between pro- and anti-inflammatory microglial functions might constitute a crucial component of PD onset and progression. Cumulated data also suggest that, during PD, microglia might lose beneficial functions and gain detrimental ones, in addition to mediating inflammation. In this mini-review, we aim to summarize the literature discussing the functional and morphological changes that microglia undergo in PD pathophysiology and upon exposure to its two main environmental risk factors, aging, and chronic stress.